PSV-13 Lawsonia Intracellularis Increases Cell Proliferation in Swine Enteroids in Vitro. (12th April 2022) - Klaeui, Caitlin; Medida, Ramya Lekha; Stone, Matthew; Marshall-lund, Lacey; Gebhart, Connie; Saqui-Salces, Milena
Abstract: Lawsonia intracellularis is an enteric pathogen that causes thickening of the intestinal mucosa layer resulting in malnutrition, diarrhea, and poor weight gain in swine. L. intracellularis increases intestinal cell proliferation in vivo. Swine enteroids are 3-dimensional in vitro models that can be used to study bacterial infections. The objective of this study was to evaluate cellular proliferation in swine enteroids infected by L. intracellularis . Ki-67 is a protein expressed by cells that are actively proliferating and is often used to document changes in proliferation. Swine enteroids were cultured in monolayers using transwells, infected with L. intracellularis (PHE/MN1-00), and harvested on 5, 7, and 14 d post infection (dpi). Enteroid monolayers were fixed in 4% formaldehyde overnight, and immunofluorescence for Ki-67 and L. intracellularis were performed. Experiments were replicated 3 times. Immunofluorescent staining using L. intracellularis antibodies demonstrated infection of enteroids. Cell proliferation was assessed by counting the number of Ki-67 positive cells under 20x magnification and comparing to the total number of cells as stained by 4′, 6-diamidino-2-phenylindole (DAPI) in infected and non-infected enteroids. Cell counts were analyzed using paired t-test in GraphPad Prism comparing infected enteroids with uninfected enteroids for each dpi time. Cell proliferation between non-infected and infected enteroids were not different at 5 dpi (0.014±0.007 vs. 0.044±0.021, P = 0.21) or 14 dpi (0.101±0.10 vs. 0.061±0.034, P = 0.46). However, at 7 dpi, infected enteroids showed greater cell proliferation (0.67±0.056 vs. 0.078±0.58, P = .047). In infected pigs, it was reported that increased cell proliferation is observed at 7 dpi. In vitro swine enteroids reproduce the proliferative changes observed in vivo, validating their use as a model for L. intracellularis infection.